Capsular Polysaccharide Biosynthesis from Recombinant E. coli and Chondroitin Sülfate Production - Erenler, Ayse Sebnem (Cellular and Molecular Biology, 2019)
Chondroitin sulfate (CS) is an important biomedical product. CS is the basic structural component of the mammalian extracellular matrix and is widely used in many applications in the fields of medicine, veterinary medicine, pharmaceuticals and cosmetics. For CS production, mainly animal sources are used. However, in today’s conditions, due to various risks and artificial synthesis, there has been an increase in alternative sources of production methods for CS, instead of using animal resources. In this study as a powerful alternative microbial production of CS has been targeted. By using recombinant E. coli strains to integrate VHb /vgb+ and kfo+ systems, the aim was to obtain high purity CS from reliable biotechnological processes. Plasmid pUC8:15 bearing the vgb gene region, and plasmid pETM6-PACF carrying the kfoA, kfoC and kfoF genes responsible for chondroitin synthesis, were transferred to E. coli bacteria. Microbial CS was obtained by adding sulfate groups to chondroitin acquired after the treatments. The results were confirmed by HPLC and NMR analyses. The product, compared to its counterparts, was found to be an effective drug, potentially with a low molecular weight value.